2023
DOI: 10.1039/d3ob00324h
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent sensing of non-steroidal anti-inflammatory drugs naproxen and ketoprofen by dansylated squaramide-based receptors

Abstract: Bis-squaramide receptors L1–L4 bearing a dansyl moiety were synthesised and their potential applications as fluorescent probes towards non steroidal anti-inflammatory drugs naproxen and ketoprofen was investigated. A detailed photophysical characterization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…As expected, under these novel experimental conditions, we were still able to calculate the association constants for the formation of the 1:2 adducts and to confirm the strong affinity of L4 toward the anionic guests, even in this more competitive medium. In the case of L5 , the results of the 1 H NMR solution studies with both NaNS and NaKF have been reported elsewhere and demonstrate the formation of 1:2 adducts with a stronger affinity to NS – …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As expected, under these novel experimental conditions, we were still able to calculate the association constants for the formation of the 1:2 adducts and to confirm the strong affinity of L4 toward the anionic guests, even in this more competitive medium. In the case of L5 , the results of the 1 H NMR solution studies with both NaNS and NaKF have been reported elsewhere and demonstrate the formation of 1:2 adducts with a stronger affinity to NS – …”
Section: Resultsmentioning
confidence: 99%
“…In comparison to L1 , the introduction of two supplementary H-bond donor groups in the structure of L5 resulted in a better sensitivity to KF – for membrane mb 5.2 (44.1 ± 4.5 mv/dec) containing 50 mol % cationic sites with respect to the ionophore (see Figure S22). Interestingly, while L1 forms with KF – only the 1:1 adduct in the DMSO/H 2 O mixture (see Table ), L5 forms the 1:2 adduct in the same experimental conditions . Similar to membranes based on L4 , the super-Nernstian slopes observed for the bigger-sized NS – anion indicate the formation of a mixture of 1:1 and 1:2 adducts inside the membrane phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5). 19,20 The macrocyclic systems 16 and 17 have been found to be able to bind ketoprofen in its anionic form in a 1 : 1 stoichiometry in CH 3 CN/DMSO solution (1 : 1 v/v) with association constants of K ass = 9.4 Â 10 4 AE 0.6% and K ass = 8.3 Â 10 4 M À1 AE 1%, respectively. Receptors 19-24 were employed successfully for developing ion selective electrodes (ISEs) able to discriminate ketoprofen and naproxen in their anionic forms in real samples.…”
Section: Claudia Caltagironementioning
confidence: 99%